Colleges and Universities as Agents of Social Change - California Univ., Berkeley. Center for Research and Development in Higher Education; Minter, W., John; Thompason, Ian M.; California Univ., Berkeley. Center for Research and Development in Higher Education; Western Interstate Commission for Higher Education, Boulder, CO. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
Papers of the Tenth Annual College Self-Study Institute, held in 1968, are presented. They include: "Colleges and Universities as Agents of Social Change: An Introduction," by T.R. McConnell; "Agent of Whom?" by Harris L. Wofford, Jr.; "The University as an Instrument of Social Action," by Roger W. Heyns; "The Tightening Tension: The University's External Relations," by Eldon L. Johnson; "Colleges and Universities as Agents of Social Change: Goals and Conflicts," by Algo D. Henderson; and "The University as an Economic and Social Unit," by Kenneth E. Boulding. A 108-item annotated bibliography is also included. (LBH)
Availability: Western Interstate Commission for Higher Education, Boulder, Colorado ($3.50).
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bibliographies; Change Agents; College Role; Colleges; Community Relations; Conference Reports; Conferences; Higher Education; School Community Relationship; Social Change; Social Problems; Universities; College Self Study Institute; Collected Works, Proceedings